Establishment of dna isolation protocol from Sarawak sea turtle eggs - Tan, Kim Hock (Universiti Malaysia Sarawak, UNIMAS, 2010)
Chelonia mydas has been listed in IUCN List as endangered species due to continuous human exploitation. Although there are laws and legislations in protecting this endangered species, turtle eggs are still able to be found sold illegally in the black market in Malaysia. Eggs poachers claimed that the turtle eggs are obtained from foreign countries in order to escape from prosecution. Hence, in this study, three DNA extraction methods have been evaluated in term of DNA yield and amplification quality. Out of three extraction methods, CTAB extraction method produced highest DNA yield from the yolks samples but it is relatively not pure. Besides that, Guanidinium Isothiocyanate Extraction method gives pure DNA but low in concentration. Phylogenetic trees based on D-loop gene sequenced from turtles’ eggs showed that it has very close relationship with sample from Satang Island.